Anthropometry, Fatty Liver, Plasma Lipid, and Adipose Tissue on Rat Wistar Induced Low-Protein Diet - Handayani, Dian; Kusumastuty, Inggita; Tritisari, Kanthi Permaningtyas; Ekawati, Laily; Galuh, Glaveria; Muniro, Lailatul; Satya, Lega; Supratiwi, Ratih Indah; Mahmudah, Anis (Journal of Tropical Life Science, 2017)
Protein energy malnutrition problem still exists in developing country. In fact, Indonesia has faced it as double burden of nutrition problems. This study aims to develop a standardized diet for developing protein energy malnutrition (PEM) on the rat to support nutrition research. Low-protein modified AIM-93M diet (LP) has been given to rats for 12 weeks intervention compared to normal protein diet (ND). Anthropometry, plasma lipid, fatty liver and the weight of adipose tissue have been analysed. The LP group showed a significantly lower body weight, body length and waist circumference (p < 0.05), a more fatty liver marker shown in LP compared to ND (p < 0.05). This study suggests that giving low protein modified AIN-M93 diet promotes protein energy malnutrition in the rat.